Preparation, Characterization and Dissolution of Solid Dispersion of Diclofenac Sodium Using Eudragit E-100 - Ehsaneh Jafari (Journal of Applied Pharmaceutical Science, 2013)
Solis dispersions (SDs) traditionally have been used as effective methods to improve the dissolution properties and bioavailability of poorly water-soluble drugs. Diclofenac Sodium, a non steroidal anti-inflammatory drug with analgesic and anti-inflammatory property was selected as the model drug. The poor aqueous solubility of the drug results in variable dissolution rate and hence poor bioavailability. The aim of the present study was to improve the solubility and dissolution rate of a poorly water-soluble drug, diclofenac sodium, by SD technique as using Eudragit E100. SD was prepared by solvent evaporation technique. The SD was characterized for particle size, particle size distribution and solubility studies. Solid state characterizations i.e., Differential Scanning Calorimetry and Scanning Electron Microscopy were also carried out for the best formulation. It was concluded that the SD prepared by solvent evaporation technique using Eudragit E100 enhanced solubility and dissolution and hence better patient compliance and effective therapy.
Keywords: Solid Dispersion, solubility enhancement, solvent ev